2020
DOI: 10.1155/2020/8263598
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Thalidomide on High-Glucose-Induced Podocyte Injury through In Vitro Modulation of Macrophage M1/M2 Differentiation

Abstract: Objective. It has been shown that podocyte injury represents an important pathological basis that contributes to proteinuria and eventually leads to kidney failure. High glucose (HG) activates macrophage polarization, further exacerbating HG-induced podocyte injury. Our previous study on diabetic nephropathy rats indicated that thalidomide (Tha) has renoprotective properties. The present study explored the effects of Tha on mRNA and protein expressions of inducible nitric oxide synthase (iNOS), tumor necrosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…The HG-induced IL-1β release in human macrophages ( 51 ). In RAW264.7 macrophages, HG significantly increased the mRNA level, as well as the release of IL-1 and TNF-α ( 52 54 ). Though the role of Gal-3 in macrophage activation and proinflammation has been studied, its involvement in HG-induced inflammatory cytokine release has not been identified.…”
Section: Discussionmentioning
confidence: 99%
“…The HG-induced IL-1β release in human macrophages ( 51 ). In RAW264.7 macrophages, HG significantly increased the mRNA level, as well as the release of IL-1 and TNF-α ( 52 54 ). Though the role of Gal-3 in macrophage activation and proinflammation has been studied, its involvement in HG-induced inflammatory cytokine release has not been identified.…”
Section: Discussionmentioning
confidence: 99%
“…A mechanistic study demonstrated that Tim-3 aggravates podocyte injury by promoting macrophage activation via the TNF-α pathway ( 54 ). Apart from TNF-α, a number of inflammatory factors, including IL-1β ( 55 ) and NO ( 53 ), take part in the inflammatory process and contribute to podocyte injury via macrophage polarization. The present study confirmed that Bud and curcumin indirectly protected against podocyte injury by modulating M1/M2 polarization via a reduction in TNF-α, NO and IL-1β levels.…”
Section: Discussionmentioning
confidence: 99%
“…Other compounds like hyperoside [193], astragalus mongholicus Bunge and Panax notoginseng formula (A&P) [194], thalidomide [195], trichosanthes kirilowii lectin (TKL) [196], and schisandrin C [197] have been found to decrease renal inflammation in mice with type 2 diabetes by modulating macrophage polarization, facilitating the transition from M1 to M2 polarization.…”
Section: Adoption Of Macrophage Polarization Toward M2 Phenotypementioning
confidence: 99%